Factoring Polynomials

Slides:



Advertisements
Similar presentations
Factoring Polynomials
Advertisements

Factoring Polynomials
6.3 Factoring Trinomials II Ax 2 + bx + c. Factoring Trinomials Review X 2 + 6x + 5 X 2 + 6x + 5 (x )(x ) (x )(x ) Find factors of 5 that add to 6: Find.
Factoring Polynomials Digital Lesson. Copyright © by Houghton Mifflin Company, Inc. All rights reserved. 2 Greatest Common Factor The simplest method.
Math 20-1 Chapter 4 Quadratic Equations
MATH!!! EXAM PREP!!!! ConoR RoweN. Addition Property (of Equality) Multiplication Property (of Equality). If the same number is added to both sides of.
10.1 Adding and Subtracting Polynomials
Solving Quadratic Equations Section 1.3
Copyright © Cengage Learning. All rights reserved.
Factoring Polynomials
Copyright © 2011 Pearson Education, Inc. Publishing as Prentice Hall. Chapter 11 Factoring Polynomials.
U4L3 Solving Quadratic Equations by Completing the Square.
Factoring Polynomials
For Common Assessment Chapter 10 Review
6.6 Quadratic Equations. Multiplying Binomials A binomial has 2 terms Examples: x + 3, 3x – 5, x 2 + 2y 2, a – 10b To multiply binomials use the FOIL.
Copyright © 2015, 2011, 2007 Pearson Education, Inc. 1 1 Chapter 6 Factoring.
Solving Quadratics: Factoring. What is a factor? Numbers you can multiply to get another number 2  3.
Slide Copyright © 2009 Pearson Education, Inc. 6.9 Solving Quadratic Equations by Using Factoring and by Using the Quadratic Formula.
Factoring Polynomials by Completing the Square. Perfect Square Trinomials l Examples l x 2 + 6x + 9 l x x + 25 l x x + 36.
REVIEW OF FACTORING Chapters 5.1 – 5.6. Factors Factors are numbers or variables that are multiplied in a multiplication problem. Factor an expression.
Copyright © Cengage Learning. All rights reserved. Factoring Polynomials and Solving Equations by Factoring 5.
PERFECT SQUARE TRINOMIALS
Factoring trinomials ax² + bx +c a = any number besides 1 and 0.
ALGEBRA 2 – CHAPTER 5 QUADRATICS. 5-2 PROPERTIES OF PARABOLAS.
Adding and Subtracting Polynomials Multiplying Polynomials Factoring Polynomials.
Solving Quadratic Equations by Completing the Square.
Lesson 2-3 The Quadratic Equation Objective: To learn the various ways to solve quadratic equations, including factoring, completing the square and the.
Factoring Quadratic Expressions Lesson 4-4 Part 1
Solving Quadratic Equations by Completing the Square
Graphing Quadratic Functions Solving by: Factoring
Factoring Polynomials
Warm up Copyright © by Houghton Mifflin Company, Inc. All rights reserved.
Polynomial Equations and Factoring
Objectives Solve quadratic equations by factoring.
Solving Quadratic Equations by Completing the Square
Solving Quadratic Equations by Completing the Square
Copyright © Cengage Learning. All rights reserved.
Factoring Polynomials
a*(variable)2 + b*(variable) + c
Factoring Polynomials
Factoring Polynomials
Factoring Special Cases
Solving Quadratic Equations by Completing the Square
Section 4.7 Solving Quadratic Equations by Completing the Square
Solving Quadratic Equations by Completing the Square
Solving Quadratic Equations by Completing the Square
Solving Quadratic Equations by Completing the Square
Solving Quadratic Equations by Completing the Square
Solving Quadratic Equations by Completing the Square
Solving Quadratic Equations by Completing the Square
Solving Quadratic Equations by Completing the Square
Solving Quadratic Equations by Completing the Square
The Square Root Property and Completing the Square
Solving Quadratic Equations by Completing the Square
Quadratic Equations and Functions
Solving Quadratic Equations by Completing the Square
The Greatest Common Factor
Solving Quadratic Equations by Completing the Square
Solving Quadratic Equations by Completing the Square
Solving Quadratic Equations by Completing the Square
Solving Quadratic Equations by Completing the Square
Factoring Polynomials
6-3 Completing the Square
Solving Quadratic Equations by Completing the Square
Solving Quadratic Equations by Completing the Square
Solving Quadratic Equations by Completing the Square
Solving Quadratic Equations by Completing the Square
Solving Quadratic Equations by Completing the Square
Solving Quadratic Equations by Completing the Square
Solving Quadratic Equations by Completing the Square
Presentation transcript:

Factoring Polynomials

Greatest Common Factor The simplest method of factoring a polynomial is to factor out the greatest common factor (GCF) of each term. Example: Factor 18x3 + 60x. 18x3 = 2 · 3 · 3 · x · x · x Factor each term. = (2 · 3 · x) · 3 · x · x 60x = 2 · 2 · 3 · 5 · x = (2 · 3 · x) · 2 · 5 GCF = 6x Find the GCF. 18x3 + 60x = 6x (3x2) + 6x (10) Apply the distributive law to factor the polynomial. = 6x (3x2 + 10) Check the answer by multiplication. 6x (3x2 + 10) = 6x (3x2) + 6x (10) = 18x3 + 60x Copyright © by Houghton Mifflin Company, Inc. All rights reserved. Greatest Common Factor

A common binomial factor can be factored out of certain expressions. Example: Factor 4x2 – 12x + 20. GCF = 4. = 4(x2 – 3x + 5) Check the answer. 4(x2 – 3x + 5) = 4x2 – 12x + 20 A common binomial factor can be factored out of certain expressions. Example: Factor the expression 5(x + 1) – y(x + 1). 5(x + 1) – y(x + 1) = (x + 1) (5 – y) (x + 1) (5 – y) = 5(x + 1) – y(x + 1) Check. Copyright © by Houghton Mifflin Company, Inc. All rights reserved. Example: Factor

A difference of two squares can be factored using the formula a2 – b2 = (a + b)(a – b). Example: Factor x2 – 9y2. x2 – 9y2 = (x)2 – (3y)2 Write terms as perfect squares. = (x + 3y)(x – 3y) Use the formula. The same method can be used to factor any expression which can be written as a difference of squares. Example: Factor (x + 1)2 – 25y 4. (x + 1)2 – 25y 4 = (x + 1)2 – (5y2)2 = [(x + 1) + (5y2)][(x + 1) – (5y2)] = (x + 1 + 5y2)(x + 1 – 5y2) Copyright © by Houghton Mifflin Company, Inc. All rights reserved. Difference of Squares

Examples: 1. Factor 2xy + 3y – 4x – 6. Some polynomials can be factored by grouping terms to produce a common binomial factor. Examples: 1. Factor 2xy + 3y – 4x – 6. Notice the sign! 2xy + 3y – 4x – 6 = (2xy + 3y) – (4x + 6) Group terms. = y (2x + 3) – 2(2x + 3) Factor each pair of terms. = (2x + 3) ( y – 2) Factor out the common binomial. 2. Factor 2a2 + 3bc – 2ab – 3ac. 2a2 + 3bc – 2ab – 3ac = 2a2 – 2ab + 3bc – 3ac Rearrange terms. = (2a2 – 2ab) + (3bc – 3ac) Group terms. = 2a(a – b) + 3c(b – a) Factor. = 2a(a – b) – 3c(a – b) b – a = – (a – b). = (a – b) (2a – 3c) Factor. Copyright © by Houghton Mifflin Company, Inc. All rights reserved. Examples: Factor

Therefore, x2 + 3x + 2 = (x + 1)(x + 2). To factor a simple trinomial of the form x2 + bx + c, express the trinomial as the product of two binomials. For example, x2 + 10x + 24 = (x + 4)(x + 6). Factoring these trinomials is based on reversing the distributive property process. Example: Factor x2 + 3x + 2. Express the trinomial as a product of two binomials with leading term x and unknown constant terms a and b. x2 + 3x + 2 = (x + a)(x + b) = x2 + bx + ax + ba Multiply the binomials. = x2 + (b + a) x + ba Since ab = 2 and a + b = 3, it follows that a = 1 and b = 2. = x2 + (1 + 2) x + 1 · 2 (Product-sum method) Therefore, x2 + 3x + 2 = (x + 1)(x + 2). Copyright © by Houghton Mifflin Company, Inc. All rights reserved. Factor x2 + bx + c

It follows that both a and b are negative. Example: Factor x2 – 8x + 15. x2 – 8x + 15 = (x + a)(x + b) = x2 + (a + b)x + ab Therefore a + b = -8 and ab = 15. It follows that both a and b are negative. Sum Negative Factors of 15 - 1, - 15 -15 -3, - 5 - 8 x2 – 8x + 15 = (x – 3)(x – 5). Check: = x2 – 8x + 15. (x – 3)(x – 5) = x2 – 5x – 3x + 15 Copyright © by Houghton Mifflin Company, Inc. All rights reserved. Example: Factor

two positive factors of 36 13 36 Example: Factor x2 + 13x + 36. x2 + 13x + 36 = (x + a)(x + b) = x2 + (a + b) x + ab Therefore a and b are: two positive factors of 36 Sum Positive Factors of 36 whose sum is 13. 1, 36 37 2, 18 20 15 3, 12 4, 9 13 6, 6 12 = (x + 4)(x + 9) x2 + 13x + 36 Check: (x + 4)(x + 9) = x2 + 9x + 4x + 36 = x2 + 13x + 36. Copyright © by Houghton Mifflin Company, Inc. All rights reserved. Example: Factor

Example: Factor Completely A polynomial is factored completely when it is written as a product of factors that can not be factored further. Example: Factor 4x3 – 40x2 + 100x. 4x3 – 40x2 + 100x The GCF is 4x. = 4x(x2 – 10x + 25) Use distributive property to factor out the GCF. = 4x(x – 5)(x – 5) Factor the trinomial. Check: 4x(x – 5)(x – 5) = 4x(x2 – 5x – 5x + 25) = 4x(x2 – 10x + 25) = 4x3 – 40x2 + 100x Copyright © by Houghton Mifflin Company, Inc. All rights reserved. Example: Factor Completely

Factoring Polynomials of the Form ax2 + bx + c Factoring complex trinomials of the form ax2 + bx + c, (a  1) can be done by decomposition or cross-check method. Example: Factor 3x2 + 8x + 4. 3  4 = 12 Decomposition Method 2. We need to find factors of 12 1, 12 2, 6 3, 4 1. Find the product of first and last terms is 8 whose sum 3. Rewrite the middle term decomposed into the two numbers 3x2 + 2x + 6x + 4 = (3x2 + 2x) + (6x + 4) 4. Factor by grouping in pairs = x(3x + 2) + 2(3x + 2) = (3x + 2) (x + 2) 3x2 + 8x + 4 = (3x + 2) (x + 2) Copyright © by Houghton Mifflin Company, Inc. All rights reserved. Factoring Polynomials of the Form ax2 + bx + c

Example: Factor 4x2 + 8x – 5. 4  5 = 20 1, 20 2, 10 4, 5 We need to find factors of 20 1, 20 2, 10 4, 5 is 8 whose difference Rewrite the middle term decomposed into the two numbers 4x2 – 2x + 10x – 5 = (4x2 – 2x) + (10x – 5) Factor by grouping in pairs = 2x(2x – 1) + 5(2x – 1) = (2x – 1) (2x + 5) 4x2 + 8x – 5 = (2x –1)(2x – 5) Copyright © by Houghton Mifflin Company, Inc. All rights reserved. Example: Factor

Solve by Factoring To solve a quadratic by factoring you first get the equation equal to zero and then factor. Once factored you set each expression equal to zero and solve for the variable. Copyright © by Houghton Mifflin Company, Inc. All rights reserved.

Solving Quadratic Equations by Completing the Square

Perfect Square Trinomials Examples x2 + 6x + 9 x2 - 10x + 25 x2 + 12x + 36

Creating a Perfect Square Trinomial In the following perfect square trinomial, the constant term is missing. X2 + 14x + ____ Find the constant term by squaring half the coefficient of the linear term. (14/2)2 X2 + 14x + 49

Perfect Square Trinomials Create perfect square trinomials. x2 + 20x + ___ x2 - 4x + ___ x2 + 5x + ___ 100 4 25/4

Solving Quadratic Equations by Completing the Square Solve the following equation by completing the square: Step 1: Move quadratic term, and linear term to left side of the equation

Solving Quadratic Equations by Completing the Square Step 2: Find the term that completes the square on the left side of the equation. Add that term to both sides.

Solving Quadratic Equations by Completing the Square Step 3: Factor the perfect square trinomial on the left side of the equation. Simplify the right side of the equation.

Solving Quadratic Equations by Completing the Square Step 4: Take the square root of each side

Solving Quadratic Equations by Completing the Square Step 5: Set up the two possibilities and solve

Completing the Square-Example #2 Solve the following equation by completing the square: Step 1: Move quadratic term, and linear term to left side of the equation, the constant to the right side of the equation.

Solving Quadratic Equations by Completing the Square Try the following examples. Do your work on your paper and then check your answers.

The Quadratic Formula.

What Does The Formula Do ? The Quadratic formula allows you to find the roots of a quadratic equation (if they exist) even if the quadratic equation does not factorise. The formula states that for a quadratic equation of the form : ax2 + bx + c = 0 The roots of the quadratic equation are given by :

Example 1 Use the quadratic formula to solve the equation : x 2 + 5x + 6= 0 Solution: x 2 + 5x + 6= 0 a = 1 b = 5 c = 6 x = - 2 or x = - 3 These are the roots of the equation.

Example 2 Use the quadratic formula to solve the equation : 8x 2 + 2x - 3= 0 Solution: 8x 2 + 2x - 3= 0 a = 8 b = 2 c = -3 x = ½ or x = - ¾ These are the roots of the equation.

Example 3 Use the quadratic formula to solve the equation : Use the quadratic formula to solve the equation : 8x 2 - 22x + 15= 0 8x 2 - 22x + 15= 0 Solution: Solution: 8x 2 - 22x + 15= 0 8x 2 - 22x + 15= 0 a = 8 b = -22 c = 15 a = 8 b = -22 c = 15 x = 3/2 or x = 5/4 x = 3/2 or x = 5/4 These are the roots of the equation. These are the roots of the equation.

Example 4 Use the quadratic formula to solve for x to 2 d.p : 2x 2 +3x - 7= 0 Solution: 2x 2 + 3x – 7 = 0 a = 2 b = 3 c = - 7 x = 1.27 or x = - 2.77 These are the roots of the equation.